SERVICE INNOVATION THROUGH THE COMPLETELY ORDERLY POPULATION ADMINISTRATION PROGRAM (TERSIPU) AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF ACEH TAMIANG REGENCY - Amani, Tengku Naila; Aisyah, Ti; Maryam, Maryam; Arinanda, Arinanda; Hasyem, Muhammad (Bajang Institute, 2024)
Population services are one of the public services needed by the community. Problems complained about by the community prompted the Department of Population and Civil Registration of Aceh Tamiang Regency to make a new breakthrough in the form of an innovation aimed at facilitating the community in receiving services. This innovation is the TERSIPU (Orderly Complete Population Administration) program. The purpose of this study is to determine whether the TERSIPU program has been maximally implemented and the obstacles to the TERSIPU program at the Department of Population and Civil Registration of Aceh Tamiang Regency. The method used is an inductive qualitative method. This study uses Rogers' innovation attributes, namely: 1) Relative Advantage, 2) Compatibility, and 3) Complexity. Data collection techniques are through observation, interviews, and documentation. The results of the study indicate that the TERSIPU program has been implemented since 2020. The results obtained on the Relative Advantage aspect show that the benefits obtained are a proactive approach, quick document processing, and immediate issuance. In the Compatibility aspect, the TERSIPU program is in accordance with the problems and needs of the community in Aceh Tamiang Regency. In the Complexity aspect, network constraints in several remote areas hinder service delivery. The obstacles faced by the TERSIPU program are the budget, which only comes from the Regional Revenue and Expenditure Budget (APBD) and is very limited, as well as the lack of community participation in the TERSIPU program. The optimization of the well-run service is expected to continue to operate well in the future.